PENGARUH STRATEGI DIFERENSIASI TERHADAP KEPUASAN PELANGGAN INDUSTRI JASA PENGIRIMAN (KASUS PT. POS INDONESIA CABANG PEKANBARU) - Riama Desy Hotmauli Sibuea; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at PT. Pos Indonesia Pekanbaru, located at Sudirman Street 229,Pekanbaru. The study was purpose to determine the influence of differentiation strategy on customer satisfaction at PT. Pos Indonesia Pekanbaru.Methodology that use in this research are descriptive and quantitative with SPSS, and the population of this study are the customers of PT. Pos Indonesia Pekanbaru. Formula Slovin is used for the sampling, sampling method with accidental sampling as many as 100 people. The form of research data are primary data and secondary data, with the questionnaire as the research instrument.From the results of data analysis include validity, reliability, simple linear regression, t-test, and the test of determination (R2). The results showed that the strategy of differentiation significantly influence customer satisfaction. It can be seen from the value t count = 10.444 > t-table = 1,984. So that the figures obtained R2 (R Square) of 0.527 or 52.7%. This shows that the percentage contribution of independent variables (differentiation strategy) on the dependent variable (customer satisfaction) amounted to 52.7% and strong relationships with a large award is 0.52. While the remaining percentage of 47.3% (100% - 52.7%) influenced by other variables not included in this study variables.Keywords: strategy differentiation, customer satisfaction, PT. Pos Indonesia Pekanbaru